Effect of Heat Treatment on Corrosion Behaviour of Welded AA6061 Aluminium Alloy in Seawater - Nur Azhani, Abd Razak; Juliawati, Alias; L. H., Shah; M., Ishak (2012)
The effect of various heat treatments on the corrosion behaviour of welded AA6061 aluminium alloy was investigated. Gas tungsten arc welding (GTAW) was used for welding butt joint specimens. Corrosion behaviour was determined in seawater solution using potentiodynamic polarization method. Microstructure and compositional analysis of base metal (BM) and weld metal (WM) was studied with scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS). The result indicated that BM consists of Fe-rich coarse intermetallic particles that behave as cathodic sites with respect to the matrix. Tafel plot showed that WM is cathode and give better corrosion resistance in different heat treatment compared to BM. Localized corrosion was observed on the corroded surfaces by SEM.